Sensitization to docetaxel in prostate cancer cells by green tea and quercetin - Wang, Piwen (J Nutr Biochem, 2015)
Chemotherapy with docetaxel (Doc) is a standard treatment for metastatic and castration-resistant prostate cancer. However, chemoresistance and side effects of Doc limit its clinical success. We investigated whether natural products green tea (GT) and quercetin (Q), a flavonoid from apples and onions, will enhance the efficacy of Doc in androgen-independent (AI) prostate cancer cells. Two cell lines including LAPC-4-AI and PC-3 were treated in vitro with 40μM of (−)-epigallocatechin gallate (EGCG), 5μM of Q, 2nM or 5nM of Doc alone or in combination. The mixture of EGCG+Q+Doc increased the anti-proliferative effect by 3-fold in LAPC-4-AI cells and 8-fold in PC-3 cells compared to Doc alone. EGCG, Q and Doc in combination significantly enhanced cell cycle arrest at G2/M phase and increased apoptosis in both LAPC-4-AI and PC-3 cells compared to Doc alone. The mixture increased the inhibition of PI3K/Akt and the signal transducer and activator of transcription (Stat) 3 signaling pathways compared to Doc alone, and decreased the protein expression of multidrug resistance-related protein (MRP1). In addition, the combination with EGCG and Q increased the inhibition of tumor cell invasion and colony formation in both LAPC-4-AI and PC-3 cells compared to Doc alone, and decreased the percentage of CD44(+)/CD24(−) stem-like LAPC-4-AI cells. In summary, GT and Q enhanced the therapeutic effect of Doc in castration-resistant prostate cancer cells through multiple mechanisms including the downregulation of chemoresistance-related proteins. This study provides a novel therapeutic modality to enhance the efficacy of Doc in a non-toxic manner.